The Effect of Fertilisation on the Performance of Barlinka Table Grapes on Sandy Soil, Hex River Valley - Saayman, D.; Lambrechts, J.J.N. (South African Journal of Enology and Viticulture, 2017)
The response of Barlinka table grapes on grayish, sandy soil to irrigation-applied N fertilisation levels, patterns of N application, crop load and stock P and K fertilisation, were evaluated over a 12-year period in the Hex River Valley. Under the conditions of the trial, an N level of about 100 kg ha-1 appeared to be optimum for shoot growth and grape quality. Bunch and crop mass benefited from increased N levels, apparently due to better berry set. Increased N levels also appeared to preserve greenness of bunch stems better during cold storage but N levels higher than 105-120 kg ha-’ reduced colour and sugar content of berries. Applying 67% of total seasonal N during the pre-bloom to veraison period and the rest after harvest, as against a 50:50 distribution, had a slight, positive effect on shoot growth and bunch size, again apparently caused by better berry set. Indications of a small, positive response of shoot growth to stock P fertilisation were obtained. Potassium applied in this manner was found to be ineffective due to leaching and regular irrigation-applied K fertilisation had to be adopted. Increased crop load had a marked negative effect on shoot growth and grape quality, in the latter case comparable in magnitude to that of too high N levels. A balanced crop load of 22 bunches per vine with a shoot mass of 1,822 kg, was calculated for this trial, but a crop load of 18-19 bunches per vine appeared to be the maximum that still ensured the best quality.